THE HUMAN RIGHT TO EDUCATION FOR PEOPLE PRIVATELY OF THEIR FREEDOM AND HOW PRISON INCLUDES OTHER PRIVATIONS DEGRADING SUBJECTIVITY AND REDEFINES RIGHTS (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
Preliminarily we say that although much has been written on the subject of the right to education, prison inmates, we'll stick here to the analysis of the state receiving the right to education as a human right at supranational level by the International Covenant on Economic, Social and Cultural rights (ICESCR) rights and other international norms and national and local rules, to describe trunk mind that right and its implications as such, in general, and for persons deprived of their liberty by criminal disputes in particular then through these logics must be with the reception in the world of being both qualitative and quantitative mind to contrast what initially believe, it is far from match.We try to outline the end some conclusions regarding the proposed theme, in order to visualize some issues that require the re formulation of public policies and practices that hamper the right to education of persons deprived of their liberty because of conflicts criminal.
Keywords: Human rights; education; persons privated of their freedom